PENERAPAN PEWARNAAN GRAF PADA PENJADWALAN WORK FROM HOME (STUDI KASUS KANTOR PENGAWASAN DAN PELAYANAN BEA DAN CUKAI TIPE MADYA PABEAN C BLITAR) - Amaliya Asyraful Hida; Rizka Rizqi Robby (JURNAL DIFERENSIAL, 2022)
The Corona virus has been endemic in Indonesia since early March and has spread widely to almost all provinces in Indonesia which has resulted in changes in various aspects of human life. Various policies have been issued to minimize the spread of COVID-19, one of which is the implementation of PSBB (Large-Scale Social Restrictions), with the enactment of PSBB, this has resulted in disruption of community activities due to restrictions in various ways, one of which is work activities. The Blitar Customs Office implements Work From Home (WFH) with a minimum rule of 50 percent of people who carry out Work From Home (WFH). The preparation of the WFH (Work From Home) schedule is an example of scheduling that must be carried out by KPPBC TMP C Blitar, To solve the scheduling problem, an analysis will be carried out using graph theory, namely coloring, and processed with the Welch-Powell Algorithm. Welch-Powell algorithm can be used to color a graph G efficiently. From research conducted using the Welch-Powell algorithm to color WFH scheduling results in a more effective schedule. The results showed that the point coloring in the General Subdivision produced four colors with a chromatic number of 4, the point coloring in the Investigation and Investigation Section produced four colors with a chromatic number of 4, the point coloring in the Treasury Section produced 5 colors with a chromatic number of 5, the dot coloring in the KIP Section resulted in 4 colors with a chromatic number of 4.